Koncepcyjne ramy elastyczności organizacji w świetle literatury przedmiotu i badań empirycznych - Osbert-Pociecha, Grażyna (A Conceptual Framework of Organization Flexibility - in the Light of Theoretical and Empirical Research, 2008)
This article presents the flexibility as an attribute of modern organization on the basis of both theoretical study and empirical research. This research concerns understanding of flexibility by practitioners and the impact some of organization features on the conceptual framework of organizational flexibility. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 183-203